TINJAUAN KOMPARASI KINERJA KEUANGAN BANK SYARIAH MELALUI PENDEKATAN ECONOMIC VALUE ADDED (EVA) - Zannati, Rachma; Wardoyo, Dwi Urip (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2016)
This study aims to determine (a) What degree of financial performance of Islamic Banking through EVA approach with samples of the two largest Islamic banks, namely PT. Bank Syariah Mandiri and PT. Bank Muamalat Indonesia, and (b) how the competition level of return on investment returns through the value of EVA in two of the company's competitors. The population in this study were all Islamic banking companies listed in Indonesia Stock Exchange. Test analysis used in this study is to test the calculation of economic value added. This study shows that (a) The level of financial performance that has economic value to the PT. Bank Syariah Mandiri and (b) the level of financial performance that has economic value to the PT. Bank Muamalat Indonesia. In addition, the competition level of return on investment to the two banks showed that each bank is able to provide economic added value for its stakeholders with the same degree of movement. Keywords: Economic Value Added (EVA), Financial Performance